Marigolds control nematodes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
African and Mexican marigolds (Tagetes species), common weeds of Africa, can substantially improve plant growth in soil infested with root knot nematodes. Trials in Tanzania have shown that, although not as effective as nematicides, Tagetes have...